Experimental evaluation of the permanent strains of open-graded aggregate materials. Issue 7 (3rd July 2021) - Nguyen, Tan Hung; Ahn, Jaehun
Abstract : In permeable pavement systems, open-graded aggregates are commonly used for base and subbase layers that allow water to store and drain. At each traffic load cycle, the permanent strain accumulates and is considered to be one of major distresses in permeable pavement systems. This study investigates the permanent strain of open-graded aggregate material using the multi-stage repeated-load triaxial test. For this purpose, the open-graded aggregate materials with three different gradations, from a single quarry, were used. Their nominal maximum aggregate sizes were 13, 25, and 40 mm. In the multi-stage repeated-load triaxial test, the specimen is subjected to five loading sequences and each sequence is comprised of six stress combinations. At each stress combination, the specimen is subjected to 10, 000 load repetitions. Based on the test results, the material parameters of the predictive model were determined and then used to predict the permanent strains of three open-graded aggregates in other loading sequences. The test results and the predictions showed that specimen whose gradation bounded by two others happened to have the highest resistance to permanent strain. Regardless of the difference in aggregate sizes, the material parameters of the open-graded aggregates did not vary significantly. In addition, open-graded aggregate materials were more dependent on bulk stress than deviator stress.